Efektivitas Metode Fonibel dalam Kemampuan Membaca Awal Siswa Sekolah Dasar (SD) Kelas 1 - Rhezandya Pradiptha Zalma; Iqbal Rahman; Nurul Aulia; Saskia Ramadhani (Culture education and technology research (Cetera), 2024)
Reading is one of the essential basic skills for children in elementary school. This study aims to evaluate the effectiveness of the fonibel method in improving reading readiness among first-grade elementary students. The fonibel method combines phonics and syllable methods to introduce letters and teach children to read through syllables. This research employs a descriptive method with observations of first-grade students in Bukittinggi. The study involved seven sessions, including rapport building, initial observation, pretest, five intervention sessions, and a posttest. Data obtained from observations, pretests, and posttests were analyzed descriptively to observe changes and developments in students' reading abilities after the intervention. The results showed that all students could pronounce all vowel and consonant letters and combine letters into syllables and words after the intervention. The fonibel method proved effective in enhancing students' reading abilities, creating a fun and interactive learning environment, and increasing student motivation and engagement in the learning process. This study provides significant contributions to the development of effective and enjoyable reading instruction methods for elementary school students.